Negatives Effects of Forestation - Osorio Sánchez, Leidy Yohana; Libarled Sánchez Bolívar, Libarled Sánchez Bolívar (Multidisciplinar (Montevideo), 2024)
Currently Colombia, from a forestry perspective, is one of the richest countries in terms of biodiversity, focusing on specific regions of the nation. The following research work shows the diverse negative effects that underlie the practice of deforestation seen from cultural and population aspects in diverse countries that form the Amazon, for which, it is approached from the conception or own construction of the definition of deforestation by means of a compilation process of investigative material; presenting the problem in the nation, from a concentration in the Amazon region, centralized in Colombia and the department of Caquetá, which aims to glimpse how deforestation affects the various populations and biodiversity present there, all the above, to present the various consequences or effects that this indiscriminate practice has, including global warming, loss of soil quality and destruction of habitats, flora and fauna